2001
DOI: 10.1093/emboj/20.17.4657
|View full text |Cite
|
Sign up to set email alerts
|

Folded HasA inhibits its own secretion through its ABC exporter

Abstract: Gram-negative bacterial proteins secreted by ABC exporters carry a secretion signal in their carboxylic extremities. This characteristic suggests that the polypeptide needs to be fully synthesized before it can be secreted and, therefore, presumably may fold at least in part before its secretion. We investigated the relationship between folding and secretion using HasA, a hemoprotein of Serratia marcescens secreted into the extracellular medium by a dedicated Has ABC exporter. We ®rst demonstrated that when Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…1 A B), most likely reflect distinctive structural features of these sequences. Thus, different folding and unfolding characteristics have been noted for the types of proteins described above [23][24][25] due to the presence of chaperone-binding sites in the type III secreted proteins which could support partially folded [24] or largely unfolded [25] Table 6 The validation of classification results by combined cross-validation and testretest procedures for multiple randomly-divided samples of amino acid composition data sets. The summary results represent 15 randomly divided samples of data sets for both variables (15x42 cases each) into test (cases selected) and retest/hold (cases not selected) samples within a range 60-80 % and 20-40 % of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1 A B), most likely reflect distinctive structural features of these sequences. Thus, different folding and unfolding characteristics have been noted for the types of proteins described above [23][24][25] due to the presence of chaperone-binding sites in the type III secreted proteins which could support partially folded [24] or largely unfolded [25] Table 6 The validation of classification results by combined cross-validation and testretest procedures for multiple randomly-divided samples of amino acid composition data sets. The summary results represent 15 randomly divided samples of data sets for both variables (15x42 cases each) into test (cases selected) and retest/hold (cases not selected) samples within a range 60-80 % and 20-40 % of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that protein translocation mediated by bacterial ABC transporters requires protein unfolding (Debarbieux and Wandersman, 2001;Sharff et al, 2001). For example, SecB, a bacterial chaperone that keeps cytoplasmic protein precursors in an unfolded state, is required for ABC transporter-dependent secretion of the bacterial protein HasA Journal of Cell Science 117 (9) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-surface staining measured in the absence of aminopterin was set to 100% and compared with cell-surface staining in the presence of aminopterin (n=3). (Debarbieux and Wandersman, 2001). It has been reported that ABC1 transporters might be involved in the overall process of unconventional secretion of interleukin 1β secretion by mammalian cells (Hamon et al, 1997;Zhou et al, 2002); however, this conclusion is based solely on pharmacological evidence.…”
Section: Discussionmentioning
confidence: 99%
“…SecB, a cytoplasmic chaperone that functions to slow the rate of folding of proteins destined for secretion by the general secretory pathway, slows the folding of HasA and is required for secretion of HasA, suggesting that HasA must be unfolded to be transported (112,418,529). If HasA is allowed to fold in the cytoplasm, it inhibits secretion of newly synthesized molecules, suggesting that the folded protein retains affinity for the transporter but is not competent for transport (109). Most proteins that are secreted by type I systems do not require SecB; instead, it has been proposed (204) that the conserved glycine-rich repeat (RTX), present in most type I substrates but absent from HasA, may serve the same function by delaying the folding process.…”
Section: Protein Trafficking Between and Across Membranesmentioning
confidence: 99%